Bioremediation of Petrol Engine Oil Contaminated Soils With Pyoverdine From Pseudomonas Putida - Ajjam, Sata (Physical Sciences, Life Science and Engineering, 2025)
The poisoning of aquatic and subterranean habitats by petroleum and its compounds is one of the most alarming environmental issues. This work proposes the use of Pseudomonas spp. for the degrading treatment of petroleum engine oil. An isolated bacterial strain from soils affected by engine oil, Pseudomonas putida, was able to manufacture pyoverdine with a higher productivity level of 18.8%. With the use of Sepharose 4B activated with epichlorhydrin the pyoverdine was isolated. It eluted as two isoforms in two peaks. The degradation of gasoline engine oil with purified pyoverdine increased over time, reaching its maximum level after nine days. As time increased, the degradation level decreased, suggesting that using microbial products as biological alternatives could be a more economical and effective way to reduce pollutants and conserve natural resources.